Analysis of factors influencing successful Agrobacterium-mediated genetic transformation in two different explants of peanut (Arachis hypogaea L.) variety BINA Chinabadam-2 - Rafiq, Sreoshee (BRAC University, 2014)
A thesis submitted to BRAC University in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology